Transport of dangerous goods in Flanders - Karola Imbrechts; Bob Gorrens; Philip Van Driessche (Chemical Engineering Transactions, 2019)
In Flanders and by extension in the whole world, accidents involving the transport of dangerous goods occur. Therefore, Flanders is developing a risk analysis and assessment system for the external human risks of transporting dangerous goods. The general outline of the system has now been established, based on a number of external research projects. The system allows to obtain a profile of the risks of serious accidents with the transportation of dangerous goods on roads, railways, waterways, pipelines and in ports. In brief, the risk analysis system consists of the following major elements: dividing of the transport routes into segments, determining the probability of a major accident per segment, determining the damage per segment, determining the risks for each segment and determining the risks per route. The next step was the developing of a risk assessment system to be able to decide whether or not the risk of the transport of dangerous goods is acceptable, whether or not extra safety measures have to be taken and which of the alternative routes is the most favourable one for external safety. The system consists of two major steps. First, the risk per segment is studied and if necessary, the ALARP principle is applied. Second, the risk of the total route is calculated for all alternative routes and is compared.